EFEKTIVITAS MODEL PROBLEM BASED LEARNING BERBANTUAN MAGIC BOX MAGLITEK UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA SD - Siti Noor Arofah; Siti Masfuah; Sekar Dwi Ardianti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Education plays an important role in producing superior human resources, but the learning outcomes of fifth-grade students of NU Mafatihul Ulum Elementary School are still low due to the dominance of conventional learning that does not involve students' direct activeness. This study focuses on improving learning outcomes through the implementation of the Problem Based Learning (PBL) model assisted by the Magic Box Maglitek media. Using a quantitative approach with a one-group pretest-posttest experimental design, this study involved twenty students through a saturated sampling technique. The research stages began with the administration of a pretest, followed by treatment using PBL syntax integrated with interactive box media, and ended with a posttest and data analysis using paired sample t-test and N-Gain tests. The quantitative research findings showed a significant increase in the average score from 60 to 83. Statistical analysis through the t test produced a significance value of 0.001 which confirmed a significant difference before and after treatment. In addition, the N-Gain score of 0.59 placed the effectiveness of this model in the moderate category. The main conclusion confirms that the integration of the PBL model and Maglitek's Magic Box is highly effective in concretizing abstract technological concepts and stimulating active student engagement. Therefore, educators are advised to adopt this concrete media innovation to continuously transform the quality of science and science learning at the elementary school level, in order to achieve adaptive and solution-oriented student competencies.